Comparative Study Between Ḥadīth And Sirah Nabawiyyah Regarding the Birth of The Prophet Muhammad - Kharis, Muhammad (AL ISNAD: Journal of Indonesian Hadith Studies, 2024)
Ḥadīth and Sirah Nabawiyyah are two things that many people think are same, but actually they are two different things. ḥādīth is certainly part of the Sirah, but the Sirah is not necessarily part of the ḥādīth. ḥādīth is the main reference source of Sirah, while Sirah is one way to understand ḥādīth. Even though different, both have an equally important role in shaping and influencing Islamic law. This study will focus on the discussion of Sirah, precisely about the history of the birth of the Prophet Muhammad. A prophet who was sent by Allah as the last prophet whose birth was accompanied by many great events that contained various lessons. In this paper, the author uses a qualitative method with descriptive-explanative analysis through a historical approach. All the events described, both when the Arabs before knowing Islam until the arrival of the Prophet have a close relationship with one another. Allah has planned it neatly and sequentially